Analisis Hukum Terhadap Pelaksanaan Perjanjian Sewa Rahim (Surrogate Mother) Ditinjau Menurut Perspektif Hukum Positif - R. Febrina Andarina Zaharnika (Jurnal Hukum Mimbar Justitia, 2021)
A uterine rental agreement or known as a "surrogate mother" is a surrogate mother classified as a method or effort of pregnancy outside the natural way. The implementation of a uterine rental agreement or surrogate mother is an agreement between a woman who binds herself through an agreement with another party (husband and wife) to become pregnant with the result of the fertilization of the husband and wife which is implanted into her womb, and after giving birth is required to give up the baby, to the husband and wife based on the agreement made. This type of research is normative juridical. The specification of this research is descriptive analytical. Data sources consist of primary, secondary and tertiary legal materials. The data collection method uses library research on secondary data. Methods of data analysis using qualitative normative methods. The results of the study, First, against the surrogate mother agreement or uterine rental, the agreement is invalid because it is based on the fourth condition in terms of the validity of an agreement Article 1320 of the Civil Code, namely due to "the existence of a lawful cause" which makes the agreement null and void. It is also invalid because it contradicts existing laws. Second, the surrogate mother's womb rental agreement will give rise to rights and obligations for the parties. If there is a dispute with the surrogate mother, the resolution can prioritize the best interests of the child.Â Keywords: Agreement, Lease, Rent Womb, Surrogate Mother.